2.47. Rozwiąż równania: a) (x – 3) * x + 7(x – 3) = 0 c) (x – 2) – x(x – 2) = 0 e) – (x – 1) * x = 9(x – 1) g) (x – 1)(x – 6) = – 2x * (x – 1) b) x ^ 2 + 4x = 0 e) 5x = – 20x ^ 2 b) 2(3x + 5) * x + 4(3x + 5) d) 3(x – 4) – (x – 4)(x – 1) f) 4x * (3x – 8) – 8(x + 5) * (3x – 8) h) 3(5x + 2) – 3(2x + 1) * (- 5x – 2) c) 5x – x ^ 2 = 0 f) – 2x ^ 2 = – 8x b) 2(x + 1) – x(x + 1) = 0 d) x(x + 5) = 3(x + 5) f) (x + 2)(x + 3) – 5(x + 3) = 0 h) (2x + 1)(x – 4) = 9(x – 4)

2.47. Rozwiąż równania: a) (x – 3) * x + 7(x – 3) = 0 c) (x – 2) – x(x – 2) = 0 e) – (x – 1) * x = 9(x – 1) g) (x – 1)(x – 6) = – 2x * (x – 1) b) x ^ 2 + 4x = 0 e) 5x = – 20x ^ 2 b) 2(3x + 5) * x + 4(3x + 5) d) 3(x – 4) – (x – 4)(x – 1) f) 4x * (3x – 8) – 8(x + 5) * (3x – 8) h) 3(5x + 2) – 3(2x + 1) * (- 5x – 2) c) 5x – x ^ 2 = 0 f) – 2x ^ 2 = – 8x b) 2(x + 1) – x(x + 1) = 0 d) x(x + 5) = 3(x + 5) f) (x + 2)(x + 3) – 5(x + 3) = 0 h) (2x + 1)(x – 4) = 9(x – 4)